Cetoacidosis Diabética Euglucémica, un diagnostico difícil de identificar - Mário Monteiro; Telma Elias; Cármen Ferreira; Daniela Brito (Sociedade Galega de Medicina Interna, 2021)
Diabetic Ketoacidosis is a serious and potentially life-threatening acute complication of Diabetes Mellitus. SGLT-2 inhibitors are recommended as first-line therapy in patients unable to tolerate metformin or as second-line agents after metformin. Their use is increasing as new data show, besides improving glycemic control, weight loss, blood pressure reduction, and beneficial cardiovascular and reno-protective effects. Euglycemic diabetic ketoacidosis is a rare but potential complication of SGLT-2 inhibitors. Physicians including internists, intensivists and emergency physicians should all be aware as this diagnosis can easily be missed in the absence of evident hyperglycemia. We report a case of 61-year-old male admitted in the emergency room because of altered mental status, associated with holocranial headache. He had medical history of type 2 diabetes and had recently started a SLGT-2 inhibitor. Arterial blood gases showed a severe high anion gap uncompensated metabolic acidosis. Blood and urine Ketones were high with normal serum glucose levels. The diagnosis of euglycemic ketoacidosis due to SLGT-2 inhibitor was made.